Factors affecting student readiness towards OBE implementation in engineering education: Evidence from a developing country - Md Shahadat Hossain Khan; Nafiu Salele; Mahbub Hasan; Benadjih Oiriddine Abdou (Heliyon, 2023)
Engineering universities in the South Asian region have been investigating the efficacy of Outcome-Based Education (OBE) in preparing their students to meet the demands of the Fourth Industrial Revolution (4IR). Evaluating students' motivations towards OBE is crucial for its successful implementation into engineering degree programs. This research aims to explore students' readiness towards OBE implementation at one of the prominent engineering universities in Bangladesh. To achieve this aim, an instrument was developed to comprehensively measure students' readiness towards the implementation of OBE. The survey instrument with a 7-point scale, measuring six constructs of the proposed model, such as (a) Students' awareness, (b) Teachers' commitment, (c) Institutional support, (d) Perceived easiness, (e) Students' motivation, and (f) Self-efficacy, was developed and administered to a pilot sample of sixty-eight participants (N = 68) from two engineering domains: Civil and Environmental Engineering (CEE), and Computer Science and Engineering (CSE). The final data was collected from a cohort of Three Hundred and Seventy participants (N = 370), distributed across four engineering domains. A structural equation modeling (SEM) with the help of the Smart-PLS software was conducted to determine the construct validity of the measurement model and to evaluate the model fit. Results from the analysis indicate no significant positive effect of teachers' commitment (TC) on students' readiness (SR). However, the results reveal a significant positive effect of students' awareness (SA) and perceived easiness (PE) on students’ readiness (SR). Results also reveal no significant moderating role of institutional support (IS) on the relation between the exogenous variables (IS, SA, PE) and the endogenous variable (SR). The research recommends Institutional Support as essential for instructors and students to implement outcome-based education (OBE) in engineering education.